High-stability monocrystalline zinc oxide quantum dots and preparation method thereof

CN122957873APending Publication Date: 2026-10-23JIANGMEN ZHUTIAN ZHONGKE TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610596215.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-30
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,现有技术在制备过程中普遍存在以下问题:一是粒径分布不均匀,难以精确控制量子点尺寸;二是表面缺陷多,影响其光学性能和生物活性;三是稳定性差,尤其是高浓度条件下易发生团聚和沉淀;四是晶体结构控制困难,难以获得单晶形态的量子点

Benefits of technology

1)通过精确控制液相化学合成工艺参数,实现了氧化锌量子点单晶形态的可控制备,晶体质量高,表面缺陷少;

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of high stability single-crystal zinc oxide quantum dots and preparation method thereof.The method is prepared by accurately controlling liquid phase chemical synthesis process parameters (such as reaction temperature, pH value, ligand type and drop adding speed etc.), successfully prepared the single-crystal zinc oxide quantum dots of uniform particle size, few surface defects.The key technology breakthrough is, by specific ligand modification, realizes the long-term stability of high concentration quantum dot dispersion liquid for more than three years under the condition of no coating or encapsulation, effectively solves the problem of easy agglomeration and precipitation.The prepared quantum dots are characterized by XRD, TEM etc.It is confirmed as single-crystal structure, and its "three-antibody" effect on bacteria (such as escherichia coli, staphylococcus aureus), virus (such as H1N1 influenza virus) and fungi (such as candida albicans) is verified, and the activity is closely related to particle size and concentration.The method is simple, low in cost, suitable for large-scale production, and has wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of nanomaterials technology, and particularly to the preparation technology of functional quantum dot materials. Specifically, it relates to a zinc oxide quantum dot with a single crystal structure and high stability and its liquid-phase chemical synthesis method, and especially to the application of this quantum dot in antimicrobial fields such as antibacterial, antiviral, and antifungal properties. Background Technology

[0002] Zinc oxide quantum dots (ZnO QDs), as an important semiconductor nanomaterial, have shown broad application prospects in biomedicine, food safety, and environmental remediation due to their unique optical properties, biocompatibility, and antimicrobial activity. Particularly in antimicrobial applications, zinc oxide quantum dots can exert antibacterial, antiviral, and antifungal effects through multiple mechanisms, including generating reactive oxygen species (ROS), disrupting cell membrane structure, and releasing zinc ions.

[0003] Currently, the main methods for preparing zinc oxide quantum dots include liquid-phase chemical synthesis methods such as sol-gel, hydrothermal, and microemulsion methods. However, existing technologies generally suffer from the following problems during preparation: first, uneven particle size distribution makes it difficult to precisely control the quantum dot size; second, numerous surface defects affect their optical properties and bioactivity; third, poor stability, especially prone to aggregation and precipitation under high concentration conditions; and fourth, difficulty in controlling the crystal structure, making it hard to obtain single-crystal quantum dots. These problems severely restrict the large-scale preparation and practical application of zinc oxide quantum dots.

[0004] There are currently some patented technologies related to the preparation and application of zinc oxide quantum dots. For example: CN112390282A discloses a hydrophilic zinc oxide quantum dot, its preparation method, and its uses. This patent uses zinc acetate dihydrate, potassium hydroxide, and APTES (3-aminopropyltriethoxysilane) as surface modifiers to prepare spherical zinc oxide quantum dots with an average particle size of less than 5 nm. These quantum dots exhibit good colloidal properties and optical stability in aqueous solution, and show strong inhibitory effects on both Gram-positive and Gram-negative bacteria, making them suitable for applications in daily cosmetics. However, this patent does not address the control of single-crystal morphology, nor does it disclose antiviral and antifungal efficacy, and it does not solve the problem of long-term stable dispersion under high concentration conditions.

[0005] CN114052125A discloses a method for large-scale preparation of zinc oxide quantum dots and their application in animal feed. This patent employs a sol-gel method, using zinc precursors and alkaline solutions as raw materials to prepare zinc oxide quantum dots with a particle size of 3-10 nm in anhydrous ethanol solvent. This method features simple reaction conditions, no waste emissions, and low cost. The prepared quantum dots possess a large specific surface area and biocompatibility, which can improve the bioavailability and antibacterial activity of zinc oxide. However, this patent primarily focuses on its application as a feed additive and does not address the preparation and characterization of single-crystal morphology, nor does it solve the problem of long-term stable dispersion under liquid conditions.

[0006] CN111994943A discloses a method for synthesizing uniformly sized silanized zinc oxide quantum dots. This patent employs a reflux condenser to dissolve zinc salts and strong alkalis separately in alcoholic organic compounds, then mix and react them. A silane coupling agent is added for surface modification, and finally, zinc oxide quantum dot powder is obtained through freeze-drying. The silanized zinc oxide quantum dots prepared by this method can be uniformly dispersed in water, avoiding the drawbacks of agglomeration and size inhomogeneity. However, the product prepared by this patent is in freeze-dried powder form, requiring redispersibility before use. It does not achieve long-term stable dispersion under liquid conditions, nor does it address the control of single-crystal morphology or systematic research on "three-anti" (antibacterial, antiviral, and antifungal) efficacy.

[0007] In summary, existing zinc oxide quantum dot preparation technologies have the following main drawbacks: (1) The crystal structure is difficult to control, making it difficult to obtain single-crystal zinc oxide quantum dots, which affects the stability of their optical properties and biological activities; (2) Uneven size distribution and low particle size control accuracy lead to unstable product performance; (3) Numerous surface defects affect the fluorescence quantum yield and antimicrobial activity of quantum dots; (4) Aggregation and precipitation are prone to occur under high concentration conditions, making it difficult to achieve long-term stable dispersion, especially under conditions without coating or encapsulation, the stability is even worse; (5) The research on antimicrobial activity is not comprehensive, lacking systematic evaluation of the "three-anti" effects such as antiviral and antifungal, as well as quantitative correlation studies on the activity with parameters such as quantum dot concentration and size; (6) It is difficult to prepare on a large scale. Existing methods have inaccurate process parameter control, poor repeatability, and are not suitable for industrial production.

[0008] Therefore, there is an urgent need to develop a new method for preparing zinc oxide quantum dots that can precisely control the single crystal morphology, size distribution, and surface quality of quantum dots, achieve long-term stable dispersion under high concentration conditions, and systematically evaluate its "three-resistance" effects to meet practical application needs. Summary of the Invention

[0009] The purpose of this invention is to overcome the aforementioned shortcomings of existing technologies and provide a highly stable single-crystal zinc oxide quantum dot and its preparation method. By precisely controlling the liquid-phase chemical synthesis process parameters (including reaction temperature, pH value, ligand type, dropping rate, etc.), the controllable preparation of single-crystal zinc oxide quantum dots is achieved, solving the physical problem of easy aggregation and precipitation of high-concentration uncoated single-crystal quantum dots. Stable dispersion of quantum dots in a single-crystal state for more than three years was achieved under encapsulation-free conditions. The "three-anti" efficacy of antiviral (such as H1N1 influenza virus), antibacterial (such as Escherichia coli and Staphylococcus aureus), and antifungal (such as Candida albicans) was systematically evaluated. The quantitative correlation between antimicrobial activity and quantum dot concentration and size was clarified, achieving the technical effects of uniform particle size, few surface defects, high stability, strong antimicrobial activity, and scalable preparation.

[0010] To achieve the above objectives, the present invention adopts the following technical solution: This invention provides a method for preparing highly stable single-crystal zinc oxide quantum dots, comprising the following steps: (1) Preparation of precursor solution: Dissolve zinc salt in an alcohol solvent, heat under reflux at 60-80℃ for 30-60 minutes, and cool to room temperature to obtain zinc precursor solution A; the zinc salt is selected from one or more of zinc acetate, zinc nitrate, zinc chloride, and zinc sulfate, preferably zinc acetate dihydrate; the alcohol solvent is selected from one or more of methanol, ethanol, isopropanol, and n-butanol, preferably anhydrous ethanol; the concentration of zinc salt in the alcohol solvent is 0.01-0.1 mol / L, preferably 0.02-0.05 mol / L; (2) Preparation of alkali source solution: The alkali source is dissolved in an alcohol solvent and fully dissolved under ultrasonic assistance. The solution is then cooled to room temperature to obtain alkali source solution B. The alkali source is selected from one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, and ammonia water, preferably potassium hydroxide. The concentration of the alkali source in the alcohol solvent is 0.02-0.2 mol / L, preferably 0.04-0.1 mol / L. The molar ratio of zinc salt to alkali source is 1:1.5 to 1:2.5, preferably 1:2. (3) Nucleation and growth: At room temperature, the alkaline source solution B is slowly added dropwise to the zinc precursor solution A at a rate of 0.5-2.0 mL / min, while maintaining magnetic stirring (300-600 rpm). After the addition is completed, the reaction is continued for 20-60 minutes to obtain a milky white turbid solution C. During this process, the pH value of the solution is controlled at 8.0-10.0, preferably 8.5-9.5; the reaction temperature is controlled at 15-35℃, preferably 20-25℃ (room temperature). (4) Surface ligand modification: Dissolve or dilute the ligand in deionized water to obtain ligand solution D; slowly add ligand solution D dropwise to turbid liquid C at a rate of 0.2-1.0 mL / min and continue stirring for 10-30 minutes; the ligand is selected from one or more of amino acids (such as cysteine, glutathione, histidine), organic amines (such as ethylenediamine, ethanolamine, 3-aminopropyltriethoxysilane), and mercapto compounds (such as mercaptoacetic acid, mercaptopropionic acid), preferably cysteine ​​or 3-aminopropyltriethoxysilane; the molar ratio of ligand to zinc salt is 0.1:1 to 1:1, preferably 0.3:1 to 0.5:1; (5) Separation and purification: After the reaction mixture is allowed to stand for 5-30 minutes, it is centrifuged at 5000-10000 rpm for 10-20 minutes, the supernatant is discarded and the white precipitate at the bottom is collected; the precipitate is washed with anhydrous ethanol 2-3 times, centrifuged for 10-15 minutes each time; the washed precipitate is redispersed in deionized water or alcohol solvent to obtain a highly stable single-crystal zinc oxide quantum dot dispersion; (6) Optional drying steps: If powder products are required, the dispersion can be dried in a vacuum drying oven at 40-60℃ for 12-24 hours, or freeze-dried to obtain zinc oxide quantum dot powder.

[0011] The highly stable single-crystal zinc oxide quantum dots prepared by this invention have the following characteristics: (1) Crystal structure: X-ray diffraction (XRD) analysis showed that it had the characteristics of a single crystal of wurtzite structure. The main diffraction peaks corresponded to the (100), (002), (101), (102), (110), (103), and (112) crystal planes, and there were no impurity peaks. (2) Morphology and size: Observed by transmission electron microscopy (TEM) and high resolution transmission electron microscopy (HRTEM), it is spherical or nearly spherical with a narrow particle size distribution and an average particle size of 3-10 nm. It can be controlled to specific sizes such as 3 nm, 5 nm, and 8 nm by adjusting the reaction conditions; HRTEM images show clear lattice stripes, confirming its single crystal structure. (3) Optical properties: In the ultraviolet-visible spectrum, it shows a characteristic absorption peak at 350-380 nm; in the fluorescence spectrum (PL), it shows a blue-green emission peak at room temperature (wavelength about 450-550 nm) and has a high fluorescence quantum yield; (4) Surface properties: Fourier transform infrared spectroscopy (FTIR) analysis showed characteristic absorption peaks of the ligands, confirming that the ligands were successfully modified on the quantum dot surface; the absolute value of the Zeta potential was greater than 20 mV, indicating good electrostatic stability; (5) Dispersion stability: It is a transparent or semi-transparent dispersion in aqueous solution or alcohol solvent. Under high concentration (≥10mg / mL) conditions, without coating or encapsulation treatment, it still maintains a single crystal state after being stored at room temperature for more than three years, without obvious agglomeration and precipitation. (6) Antimicrobial activity: It has significant inhibitory and killing effects on Gram-positive bacteria (such as Staphylococcus aureus), Gram-negative bacteria (such as Escherichia coli), viruses (such as H1N1 influenza virus), and fungi (such as Candida albicans). The antimicrobial activity is positively correlated with the concentration and size of quantum dots. At a concentration of 50-200 μg / mL, the inhibition rate against the above microorganisms can reach more than 90%.

[0012] The beneficial effects that this application can produce include: 1) By precisely controlling the process parameters of liquid-phase chemical synthesis, the controllable preparation of zinc oxide quantum dot single crystals was achieved, resulting in high crystal quality and few surface defects; 2) Narrow particle size distribution and controllable size, allowing for the preparation of quantum dots with different particle sizes in the range of 3-10 nm as needed; 3) Through ligand modification, the physical problem of easy aggregation and precipitation of high-concentration unencapsulated single-crystal quantum dots was successfully solved, and stable dispersion of quantum dots in single-crystal state for more than three years was achieved under non-encapsulation conditions; 4) The "three-anti" (antibacterial, antiviral, and antifungal) efficacy of quantum dots was systematically evaluated, and the quantitative correlation between antimicrobial activity and concentration and size was clarified, providing a scientific basis for practical applications; 5) The preparation method is simple, the reaction conditions are mild, the raw materials are readily available, the cost is low, and it is suitable for large-scale production; 6) The product has a wide range of applications and can be used in many fields such as medical and health care, food safety, environmental purification, and daily cosmetics. Detailed Implementation

[0013] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0014] Example 1 (1) Weigh 0.439 g of zinc acetate dihydrate (Zn(CH3COO)2·2H2O), dissolve it in 100 mL of anhydrous ethanol, heat under reflux at 70℃ for 45 minutes, and cool to room temperature to obtain a zinc precursor solution A with a concentration of 0.02 mol / L; (2) Weigh 0.224 g of potassium hydroxide (KOH), dissolve it in 50 mL of anhydrous ethanol, dissolve it completely under ultrasonic assistance, and cool it to room temperature to obtain an alkali source solution B with a concentration of 0.08 mol / L (the molar ratio of zinc salt to alkali source is 1:2); (3) At room temperature (25℃), the alkaline source solution B was slowly added dropwise to the zinc precursor solution A at a rate of 1.0 mL / min, while maintaining magnetic stirring (500 rpm). The pH value of the solution was monitored with a pH meter and controlled at around 9.0. After the addition was completed, the reaction was stirred for another 30 minutes to obtain a milky white turbid liquid C. (4) Weigh 0.121 g L-cysteine ​​(C3H7NO2S), dissolve it in 20 mL of deionized water to obtain ligand solution D (ligand to zinc salt molar ratio of 0.5:1); slowly add ligand solution D dropwise to turbid solution C at a rate of 0.5 mL / min, and continue stirring for 20 minutes; (5) After the reaction mixture is allowed to stand for 15 minutes, it is centrifuged at 8000 rpm for 15 minutes, the supernatant is discarded, and the white precipitate at the bottom is collected. The precipitate is washed three times with anhydrous ethanol, and centrifuged for 15 minutes each time. The washed precipitate is redispersed in 50 mL of deionized water to obtain a high-stability single-crystal zinc oxide quantum dot dispersion with a concentration of about 15 mg / mL.

[0015] Characterization results: TEM analysis showed that the quantum dots were spherical with an average particle size of 3.2 ± 0.5 nm and a narrow particle size distribution. HRTEM images showed clear lattice fringes with a lattice spacing of approximately 0.26 nm, corresponding to the (002) crystal plane of ZnO, confirming its single-crystal structure. XRD analysis showed that the diffraction peaks corresponded to the characteristic peaks of wurtzite ZnO, with no impurity peaks. PL spectroscopy showed a strong fluorescence emission peak at 480 nm. FTIR analysis showed a strong fluorescence emission peak at 2560 cm⁻¹. - ¹ There is a SH stretching vibration peak at 1580 cm⁻¹. - ¹ and 1400 cm - ¹ contains COO - The presence of symmetric and antisymmetric stretching vibration peaks confirms successful cysteine ​​modification on the quantum dot surface. A Zeta potential of -28.5 mV indicates good electrostatic stability.

[0016] Stability test: The dispersion was sealed and stored at room temperature, and samples were taken for observation every 3 months. The results showed that after 36 months of storage, the dispersion remained transparent with no obvious precipitation; TEM analysis showed that the quantum dots maintained their single-crystal morphology and the average particle size did not change significantly.

[0017] Example 2 (1) Weigh 1.098 g of zinc acetate dihydrate, dissolve it in 100 mL of anhydrous ethanol, heat under reflux at 75 °C for 50 minutes, and cool to room temperature to obtain a zinc precursor solution A with a concentration of 0.05 mol / L; (2) Weigh 0.560 g of potassium hydroxide, dissolve it in 50 mL of anhydrous ethanol, dissolve it completely under ultrasonic assistance, and cool it to room temperature to obtain an alkali source solution B with a concentration of 0.20 mol / L (the molar ratio of zinc salt to alkali source is 1:2); (3) At room temperature (25℃), the alkaline source solution B was slowly added dropwise to the zinc precursor solution A at a rate of 0.8 mL / min, while maintaining magnetic stirring (500 rpm) and controlling the pH of the solution at around 9.2; after the addition was completed, the reaction was stirred for another 40 minutes to obtain a milky white turbid liquid C; (4) Take 0.5 mL of 3-aminopropyltriethoxysilane (APTES), dilute it with 15 mL of deionized water to obtain ligand solution D (the molar ratio of ligand to zinc salt is approximately 0.4:1); slowly add ligand solution D dropwise to turbid solution C at a rate of 0.6 mL / min, and continue stirring for 25 minutes; (5) After the reaction mixture is allowed to stand for 20 minutes, it is centrifuged at 8000 rpm for 15 minutes, the supernatant is discarded, and the white precipitate at the bottom is collected. The precipitate is washed three times with anhydrous ethanol, and centrifuged for 15 minutes each time. The washed precipitate is redispersed in 50 mL of deionized water to obtain a highly stable single-crystal zinc oxide quantum dot dispersion with a concentration of about 20 mg / mL.

[0018] Characterization results: TEM analysis showed that the quantum dots were spherical with an average particle size of 5.1 ± 0.6 nm and a narrow particle size distribution; HRTEM images showed clear lattice fringes, confirming their single-crystal structure. XRD analysis showed characteristic peaks of wurtzite structure. PL spectroscopy showed a strong fluorescence emission peak at 510 nm. FTIR analysis showed a peak at 2930 cm⁻¹. - ¹ and 2850 cm - There is a CH stretching vibration peak at ¹, at 1100 cm⁻¹. - The presence of a Si-O-Si stretching vibration peak at position ¹ confirms successful APTES modification on the quantum dot surface. The Zeta potential of +32.1 mV indicates good electrostatic stability.

[0019] Stability test: After being stored at room temperature for 36 months, the dispersion remained transparent with no obvious precipitation, and the quantum dots maintained their single-crystal morphology.

[0020] Example 3 (1) Weigh 2.195 g of zinc acetate dihydrate, dissolve it in 100 mL of anhydrous ethanol, heat under reflux at 80 °C for 60 minutes, and cool to room temperature to obtain a zinc precursor solution A with a concentration of 0.10 mol / L; (2) Weigh 1.121 g of potassium hydroxide, dissolve it in 50 mL of anhydrous ethanol, dissolve it completely under ultrasonic assistance, and cool it to room temperature to obtain an alkali source solution B with a concentration of 0.40 mol / L (the molar ratio of zinc salt to alkali source is 1:2); (3) At room temperature (25℃), the alkaline source solution B was slowly added dropwise to the zinc precursor solution A at a rate of 0.5 mL / min, while maintaining magnetic stirring (500 rpm) and controlling the pH of the solution at around 9.5; after the addition was completed, the reaction was continued for 60 minutes to obtain a milky white turbid liquid C; (4) Weigh 0.363 g of L-cysteine ​​and dissolve it in 30 mL of deionized water to obtain ligand solution D (the molar ratio of ligand to zinc salt is 0.3:1); slowly add ligand solution D dropwise to turbid solution C at a rate of 0.8 mL / min and continue stirring for 30 minutes; (5) After the reaction mixture is allowed to stand for 30 minutes, it is centrifuged at 8000 rpm for 15 minutes, the supernatant is discarded, and the white precipitate at the bottom is collected. The precipitate is washed three times with anhydrous ethanol, and centrifuged for 15 minutes each time. The washed precipitate is redispersed in 50 mL of deionized water to obtain a highly stable single-crystal zinc oxide quantum dot dispersion with a concentration of about 30 mg / mL.

[0021] Characterization results: TEM analysis showed that the quantum dots were spherical with an average particle size of 8.3 ± 0.8 nm and a narrow particle size distribution; HRTEM images showed clear lattice fringes, confirming their single-crystal structure. XRD analysis revealed characteristic peaks of wurtzite structure. PL spectroscopy showed a strong fluorescence emission peak at 530 nm. The zeta potential was -25.3 mV, indicating good electrostatic stability.

[0022] Stability test: After being stored at room temperature for 36 months, the dispersion remained transparent with no obvious precipitation, and the quantum dots maintained their single-crystal morphology.

[0023] Example 4 Three zinc oxide quantum dots with different particle sizes prepared in Examples 1, 2, and 3 were selected for antibacterial activity testing. The test strains were Escherichia coli (ATCC 25922) and Staphylococcus aureus (ATCC 6538).

[0024] Test method: The minimum inhibitory concentration (MIC) was determined using the microbroth dilution method. The bacterial strain was cultured in nutrient broth until the logarithmic growth phase, and the bacterial concentration was adjusted to 1×10⁻⁶. 6CFU / mL. Zinc oxide quantum dot dispersions of different concentrations (10, 25, 50, 100, 200 μg / mL) were added to 96-well plates, with 100 μL of bacterial culture added to each well. After incubation at 37°C for 24 hours, the absorbance (OD) at 600 nm was measured. 600 ), calculate the antibacterial rate.

[0025] Test results: For E. coli: 3 nm quantum dots: MIC is 25 μg / mL, and the antibacterial rate reaches 95.2% at a concentration of 100 μg / mL; 5 nm quantum dots: MIC is 50 μg / mL, and the antibacterial rate reaches 92.8% at a concentration of 100 μg / mL; 8 nm quantum dots: MIC is 100 μg / mL, and the antibacterial rate reaches 91.5% at a concentration of 200 μg / mL.

[0026] For Staphylococcus aureus: 3 nm quantum dots: MIC is 50 μg / mL, and the antibacterial rate reaches 93.6% at a concentration of 100 μg / mL; 5 nm quantum dots: MIC is 50 μg / mL, and the antibacterial rate reaches 91.3% at a concentration of 100 μg / mL; 8 nm quantum dots: MIC is 100 μg / mL, and the antibacterial rate reaches 90.2% at a concentration of 200 μg / mL.

[0027] The results showed that zinc oxide quantum dots had significant antibacterial effects against both Gram-negative bacteria (Escherichia coli) and Gram-positive bacteria (Staphylococcus aureus). The antibacterial activity was negatively correlated with the particle size of the quantum dots; the smaller the particle size, the stronger the antibacterial activity. The antibacterial activity was positively correlated with the concentration; the higher the concentration, the higher the inhibition rate.

[0028] Example 5 The 5 nm zinc oxide quantum dots prepared in Example 2 were selected for antiviral activity testing. The test virus was H1N1 influenza virus (A / PR / 8 / 34 strain).

[0029] Test method: Using TCID 50 Antiviral activity was evaluated using the 50% tissue culture infectious dose method. MDCK cells (canine kidney cells) were seeded in 96-well plates and cultured to 80% confluence. Different concentrations (50, 100, 150, 200 μg / mL) of zinc oxide quantum dot dispersions were mixed with H1N1 virus (100 TCID50). 50Mix the ingredients and incubate at 37°C for 1 hour. Then add the mixture to cell wells and continue culturing for 48 hours. Viral titer is determined by observing cytopathic effect (CPE) and hemagglutination assay to calculate viral inhibition rate.

[0030] Test results: At a concentration of 50 μg / mL, the virus inhibition rate was 68.5%; At a concentration of 100 μg / mL, the virus inhibition rate was 85.3%; At a concentration of 150 μg / mL, the virus inhibition rate was 92.7%; At a concentration of 200 μg / mL, the virus inhibition rate was 96.8%.

[0031] The results showed that zinc oxide quantum dots had a significant inhibitory effect on H1N1 influenza virus, and the antiviral activity was positively correlated with concentration.

[0032] Example 6 The 3 nm zinc oxide quantum dots prepared in Example 1 were used to test their antifungal activity. The test strain was Candida albicans (ATCC 10231).

[0033] Test method: The MIC was determined using the micro-broth dilution method. Candida albicans was cultured on Sabouraud dextrose agar for 48 hours. Single colonies were picked and inoculated into Sabouraud dextrose broth, and incubated at 28°C for 24 hours until the logarithmic growth phase. The bacterial concentration was then adjusted to 1×10⁻⁶. 5 CFU / mL. Zinc oxide quantum dot dispersions at different concentrations (25, 50, 100, 150, 200 μg / mL) were added to 96-well plates, with 100 μL of bacterial culture added to each well. After incubation at 28°C for 48 hours, OD was measured. 600 Value, calculate the antibacterial rate.

[0034] Test results: The MIC is 50 μg / mL; At a concentration of 100 μg / mL, the antibacterial rate reached 90.5%; At a concentration of 150 μg / mL, the antibacterial rate reached 94.2%; At a concentration of 200 μg / mL, the antibacterial rate reached 97.3%.

[0035] The results showed that zinc oxide quantum dots had a significant inhibitory effect on Candida albicans, and the antifungal activity was positively correlated with concentration.

[0036] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing highly stable single-crystal zinc oxide quantum dots, characterized in that, Includes the following steps: (1) Preparation of precursor solution: Dissolve zinc salt in alcohol solvent, heat under reflux at 60-80℃ for 30-60 minutes, cool to room temperature to obtain zinc precursor solution A; (2) Preparation of alkaline source solution: The alkaline source is dissolved in an alcohol solvent and fully dissolved under ultrasonic assistance. After cooling to room temperature, alkaline source solution B is obtained. (3) Nucleation and growth: At room temperature, the alkaline source solution B is slowly added dropwise to the zinc precursor solution A at a rate of 0.5-2.0 mL / min while maintaining magnetic stirring. After the addition is completed, the reaction is stirred for 20-60 minutes to obtain a milky white turbid liquid C; wherein, the pH value of the solution is controlled at 8.0-10.0 and the reaction temperature is controlled at 15-35℃; (4) Surface ligand modification: Dissolve or dilute the ligand in deionized water to obtain ligand solution D; slowly add ligand solution D dropwise to turbid liquid C at a rate of 0.2-1.0 mL / min and continue stirring for 10-30 minutes; (5) Separation and purification: After the reaction mixture is allowed to stand for 5-30 minutes, it is centrifuged, the supernatant is discarded, the precipitate is collected and washed with anhydrous ethanol, and the washed precipitate is redispersed in deionized water or alcohol solvent to obtain a highly stable single-crystal zinc oxide quantum dot dispersion.

2. The preparation method according to claim 1, characterized in that, The zinc salt is selected from one or more of zinc acetate, zinc nitrate, zinc chloride, and zinc sulfate, preferably zinc acetate dihydrate; the concentration of the zinc salt in the alcohol solvent is 0.01-0.1 mol / L, preferably 0.02-0.05 mol / L.

3. The preparation method according to claim 1, characterized in that, The alkali source is selected from one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, and ammonia water, preferably potassium hydroxide; the concentration of the alkali source in the alcohol solvent is 0.02-0.2 mol / L, preferably 0.04-0.1 mol / L; the molar ratio of zinc salt to alkali source is 1:1.5 to 1:2.5, preferably 1:

2.

4. The preparation method according to any one of claims 1-3, characterized in that, The alcohol solvent is selected from one or more of methanol, ethanol, isopropanol, and n-butanol, preferably anhydrous ethanol; the magnetic stirring speed is 300-600 rpm.

5. The preparation method according to any one of claims 1-4, characterized in that, The ligand is selected from one or more of amino acids, organic amines, and thiol compounds; wherein the amino acids include cysteine, glutathione, and histidine; the organic amines include ethylenediamine, ethanolamine, and 3-aminopropyltriethoxysilane; and the thiol compounds include mercaptoacetic acid and mercaptopropionic acid; the molar ratio of the ligand to the zinc salt is 0.1:1 to 1:1, preferably 0.3:1 to 0.5:

1.

6. The preparation method according to any one of claims 1-5, characterized in that, The centrifugation conditions are 5000-10000 rpm for 10-20 minutes; the washing is performed 2-3 times, with each washing cycle lasting 10-15 minutes.

7. The preparation method according to any one of claims 1-6, characterized in that, It also includes step (6) drying treatment: drying the dispersion in a vacuum drying oven at 40-60℃ for 12-24 hours, or using freeze drying to obtain zinc oxide quantum dot powder.

8. A highly stable single-crystal zinc oxide quantum dot prepared by the method according to any one of claims 1-7, characterized in that, The quantum dot has the following properties: Crystal structure: It exhibits the characteristics of a single crystal with a wurtzite structure. The XRD diffraction peaks correspond to the (100), (002), (101), (102), (110), (103), and (112) crystal planes, with no impurity peaks. Morphology and size: Spherical or nearly spherical, with an average particle size of 3-10 nm and a narrow particle size distribution; HRTEM images show clear lattice fringes. Optical properties: Characteristic absorption peaks are observed in the UV-Vis spectrum at 350-380 nm; In the fluorescence spectrum, a blue-green emission peak is observed at 450-550 nm; Surface properties: The absolute value of the Zeta potential is greater than 20 mV; Dispersion stability: Under high concentrations ≥10 mg / mL, without coating or encapsulation, it still maintains a single crystal state after being stored at room temperature for more than three years; Antimicrobial activity: It has significant inhibitory and killing effects on Gram-positive bacteria, Gram-negative bacteria, viruses and fungi. At a concentration of 50-200 μg / mL, the inhibition rate can reach more than 90%.

9. The high-stability single-crystal zinc oxide quantum dot according to claim 8, characterized in that, The quantum dots are used in antibacterial, antiviral, and antifungal applications; among which, antibacterial activity includes inhibition of Escherichia coli and Staphylococcus aureus; antiviral activity includes inhibition of H1N1 influenza virus; and antifungal activity includes inhibition of Candida albicans. The antimicrobial activity is negatively correlated with the particle size of the quantum dots and positively correlated with the concentration.

10. A product comprising the highly stable single-crystal zinc oxide quantum dots as described in claim 8 or 9, characterized in that, The product is selected from one or more of the following: medical dressings, food packaging films, daily cosmetics, and environmental purification materials; wherein the quantum dot concentration in medical dressings is 0.1-5% w / w; the quantum dot concentration in food packaging films is 0.5-2% w / w; the quantum dot concentration in daily cosmetics is 0.01-1% w / w; and the quantum dot concentration in environmental purification materials is 1-10% w / w.

Citation Information

Patent Citations

  • Synthesis method of silanized zinc oxide quantum dots with uniform size

    CN111994943A

  • Hydrophilic zinc oxide quantum dot and preparation method and application thereof

    CN112390282A